Accelerated Digital Transformation : Fintech and E-Commerce as a Positive Impact of the Covid-19 Pandemic - Susilawati, Cucu (Universitas Siliwangi, 2023)
Introduction to The Problem: In 2016-2017 the fintech model in Indonesia was usually in the form of a payment system or online loan service. However, in 2019-2020 the fintech business model had 23 services. After the pandemic in Indonesia in 2020, fintech services continued to overgrow. Purpose: This study aims to explain the positive that the use of fintech has increased dramatically compared to previous years, and one of them is caused by the co-19 pandemic.Methodology: This type of research is qualitative and descriptive, and data collection methods are done with library research.Findings: This study shows that the Covid-19 pandemic made fintech and e-commerce experience a significant increase because these two products accelerate quickly. The use of fintech by both producers and consumers has at least helped people survive the pandemic. Likewise, with e-commerce, people can still meet all their living needs, especially clothing and food. The acceleration of digital transformation in Indonesia predicts that Indonesia will dominate the ASEAN internet economy in 2025.Paper Type: Research Articl